Oxytocinergic circuit from paraventricular and supraoptic nuclei to arcuate POMC neurons in hypothalamus. Issue 23 (18th October 2014) - Maejima, Yuko; Sakuma, Kazuya; Santoso, Putra; Gantulga, Darambazar; Katsurada, Kenichi; Ueta, Yoichi; Hiraoka, Yuichi; Nishimori, Katsuhiko; Tanaka, Shigeyasu; Shimomura, Kenju; Yada, Toshihiko
Abstract : Intracerebroventricular injection of oxytocin (Oxt), a neuropeptide produced in hypothalamic paraventricular (PVN) and supraoptic nuclei (SON), melanocortin‐dependently suppresses feeding. However, the underlying neuronal pathway is unclear. This study aimed to determine whether Oxt regulates propiomelanocortin (POMC) neurons in the arcuate nucleus (ARC) of the hypothalamus. Intra‐ARC injection of Oxt decreased food intake. Oxt increased cytosolic Ca 2+ in POMC neurons isolated from ARC. ARC POMC neurons expressed Oxt receptors and were contacted by Oxt terminals. Retrograde tracer study revealed the projection of PVN and SON Oxt neurons to ARC. These results demonstrate the novel oxytocinergic signaling from PVN/SON to ARC POMC, possibly regulating feeding. Abstract : Oxytocin is a new activator of ARC POMC neurons. PVN and SON oxytocin neurons project to ARC POMC neurons. PVN/SON to ARC POMC circuit could partly mediate anorexigenic action of oxytocin. Novel signaling in reverse direction from second order PVN to first order ARC.